All‐in‐One Bifunctional Oxygen Electrode Films for Flexible Zn‐Air Batteries. Issue 48 (17th October 2018) - Zeng, Sha; Tong, Xiao; Zhou, Susheng; Lv, Bo; Qiao, Jian; Song, Yanhui; Chen, Minghai; Di, Jiangtao; Li, Qingwen
Abstract: As a promising energy‐storage device, rechargeable Zn‐air batteries have attracted considerable interests. Herein, a bifunctional oxygen electrode film prepared by adhering NiCo2 O4 nanosheets to a nitrogen and oxygen dual‐doped carbon nanotubes film in a large scale is reported. The resulting self‐supporting film electrode is multifunctional, which integrates a porous conducting structure for air diffusion and charge transfer, high‐performance catalysts for oxygen reduction and evolution, and novel structural flexibility. The composite film demonstrates excellent oxygen reduction/evolution reaction catalytic activities with low Tafel slopes (50 mV dec −1 for oxygen reduction reaction; 92 mV dec −1 for oxygen evolution reaction). Without any additional current collector, gas diffusion layer, or binder, the obtained bifunctional film performs as an "all‐in‐one" air electrode in a Zn‐air battery. A 50‐cm‐long cable‐shaped Zn‐air battery based on such a film air electrode exhibits high operating potentials (≈1.2 V at 0.25 mA cm −2 ), low charging–discharging overpotentials (≈0.7 V), and stable cycling performance. Moreover, the flexible cable Zn‐air batteries show excellent stability under different deformation conditions. The proposed concept of constructing scalable, all‐in‐one, freestanding, and flexible air electrodes would pave the way to develop next‐generation wearable and portable energy‐storage devices. Abstract : Large‐scale all‐in‐one oxygen electrode films are achieved by anchoring porous spinel NiCo2 O4 nanosheets on functional carbon nanotube assemblies. Obtained freestanding air electrodes demonstrate superior oxygen reduction and evolution catalytic activities. The cable‐shaped Zn‐air batteries based on such composite air electrodes show stable charging–discharging cycles, low overpotential, and excellent flexibility.